New ways to measure well-being? A first joint analysis of subjective and objective measures - Daniela Andrén; Andrew E. Clark; Conchita D'Ambrosio; Sune Karlsson; Nicklas Pettersson (Örebro University School of Business, 2019)
Our study is, to our knowledge, the first joint analysis of subjective and objective measures of well-being. Using a rich longitudinal data from the mothers pregnancy until adulthood for a birth cohort of children who attended school in Örebro during the 1960s, we analyse in a first step how subjective (self-assessed) and objective (cortisol-based) measures of well-being are related to each other. In a second step, life-course models for these two measures are estimated and compared with each other. Despite the fact that our analysis is largely exploratory, our results suggest interesting possibilities to use objective measures to measure well-being, even though this may imply a greater degree of complexity.
Keywords: A12; D60; I31; 330; subjective and objective well-being; general life satisfaction; cortisol; birth-cohort data; adult; child and birth outcomes; multivariate imputation